The Rest of Reality. - Taulli, Tom C. (Wilson Quarterly)
Presents a letter to the editor in response to the article "Mapping the New Reality," by Steven Birkerts which deals with the implications of technology, in the spring 1992 issue of "The Wilson Quarterly."